Propuesta de personalidad docente basada en la concepción del eneagrama para desarrollar la dimensión personal en los alumnos de los institutos superiores pedagógicos - Pineda Aguilar, Walter Fernando (2009)
We proposed an alternative to develop the personal dimension based on eneagrama conception. This was applied to Education Institutes’ students in La Libertad region of Peru. We applied an eneagram test to 80 students from Nuestra Señora de la Asunción and Ciro Alegría Institutes in Otuzco to identify the kind of personality types and uncenterd features. We also applied a pre- test to determinate the development level of students’ personal dimension. This proposal was made based on the types and uncentered of students’ personality and it was developed in eight months in individual and group sessions, and by a no presential period. This took 116 pedagogic hours. The applications of the pre and post test gave these conclusions: a) In Institutes the students increased their personality levels, b) the state of students’ uncentered features got better and c) in general, this proposal based on eneagram conception let know the type of personality and uncentered features and it also let to develop students’ personal dimension.